2014
DOI: 10.1117/12.2043958
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of temporal dynamics in imagery during acute limb ischemia and reperfusion

Abstract: Ischemia and reperfusion injuries present major challenges for both military and civilian medicine. Improved methods for assessing the effects and predicting outcome could guide treatment decisions. Specific issues related to ischemia and reperfusion injury can include complications arising from tourniquet use, such as microvascular leakage in the limb, loss of muscle strength and systemic failures leading to hypotension and cardiac failure. Better methods for assessing the viability of limbs/tissues during is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In previous studies, increases in R-B values indicated increased oxygenation of the wounds through more robust microvasculature. [ 14 16 ] This is likely secondary to the increases in angiogenesis in wounds that heal compared with those that dehisce. In this study, however, we had to explore more robust normalization techniques to exploit the small differences in the R-B values between healed and dehisced wounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, increases in R-B values indicated increased oxygenation of the wounds through more robust microvasculature. [ 14 16 ] This is likely secondary to the increases in angiogenesis in wounds that heal compared with those that dehisce. In this study, however, we had to explore more robust normalization techniques to exploit the small differences in the R-B values between healed and dehisced wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in image processing allow for the immediate assessment of tissue viability, something the authors believe beneficial when treating large, heterogeneous extremity wounds. In fact, previous studies utilized a 3CCD (three charge-coupled device) camera to evaluate changes in oxygenation in red blood cells[ 12 ], vessels[ 13 ], ischemic limbs[ 14 16 ], during pediatric appendectomies[ 17 ], and in partial and donor nephrectomies[ 18 , 19 ]. The present study seeks to ascertain the imaging characteristics of a heterogeneous population of extremity wounds prior to closure using a 3CCD camera, a commercially available and inexpensive device that records the levels of each of the three primary colors (red, green, and blue) to form a high-resolution image.…”
Section: Introductionmentioning
confidence: 99%
“…Quadratic and higher-order terms indicate the temporal dynamics of the process within such overall trends and thus can capture changes in performance more finely. Functional data analysis methods have proven useful in other biomedical applications, such as modeling acute limb ischemia and reperfusion injury [49]. For modeling resilience, functional data analysis provides a natural framework for analyzing temporal changes in individual performance.…”
Section: Functional Data Analysismentioning
confidence: 99%